Genomics of clonal evolution in a rare essential thrombocythemia with coexisting Type 2 CALR and MPL S204P mutations. (31st December 2023) - Wang, Jing; Fu, Wenjing; Bao, Wenqiang; Gong, Wenyu; Xu, Shiyun; Ling, Chun; Jin, Qichuan; Zhang, Qiguo
Abstract: Essential thrombocythemia (ET) with double driver mutations is a rare disease. ET patients with both MPL and Type 1 CALR mutations have been reported. Here, we report the first case of an ET patient with both MPL S204P and Type 2 CALR mutations and a summary of our literature review findings. In the patient whose case is reported here, the disease progressed to an accelerated phase 3.5 months after diagnosis. CALR mutation disappeared and new mutations emerged as the disease progressed, such as ASXL1, CBL, ETV6, and PTPN11 mutations. This case highlights that screening for additional mutations using NGS should be considered in patients with ET to assess the prognosis, especially as the disease progresses.